The Concept of Global Transformation Labs - Rosén, Anders; Gumaelius, Lena; Nilsson, Susanne; Shibwabo, Bernard; Shayo, Eva; Ismail, Moses; Batani, John (Proceedings from the International Research Symposium on Problem-Based Learning (IRSPBL), 2025)
Global Transformation Labs (GTLs) are intended to be arenas, where students, teachers, researchers and various societal partners come together to explore and experiment with new collaborative ways of addressing global challenges and contribute to green and just transitions. The GTLs are thought to be spaces for mutual learning and reflection and places where participants can engage as change-makers, taking initiative, testing ideas and developing innovative approaches to complex societal challenges. The aim is to enhance the global perspectives of all participants, strengthen their understanding of human, societal, and planetary predicaments and opportunities, build their capabilities to navigate, act and contribute both creatively and responsibly in a changing world, and to drive transformation. This white paper presents a generative vision and an initial conceptual framework as a basis for further exploration through critical and creative conversations and co-development by interested partners.